In Search of Robert Bruce, Part II: Reassessing the Dunfermline Tomb Investigations of 1818–19. (October 2019) - MacGregor, Martin; Wilkinson, Caroline
Abstract : Building work undertaken at Dunfermline abbey in 1818 unearthed a burial vault which included a skeleton. The skull has been widely examined and has been believed to be that of King Robert I (Bruce). The present article re-examines the archaeological evidence and brings to bear the medieval historical sources on the discovery. The ailments of the king and of the body discovered in Dunfermline are discussed, as is the separate heart burial which may have been carried out upon this individual interred. A summary follows, setting the evidence for the location of the tomb uncovered in 1818 against the available historical and architectural evidence for royal burial at Dunfermline in the medieval era. The sex, age, physique, disease, heart burial, tomb location and manner of death of the body discovered are analysed to draw conclusions about the identity of the incumbent of the Dunfermline tomb.